A new species of Ptycholoma (Lepidoptera: Tortricidae) from South China - Chen, Liusheng; Jinbo, Utsugi; Wang, Min (Zootaxa, 2009)
The genus Ptycholoma Stephens, 1829 is a small Archipini genus comprised of four species distributed in the Palaearctic and Oriental Regions (Brown, 2005; Baixeras et al., 2008). Three species have been recorded from China: P. lecheana (Linneaus), P. imitator (Walsingham), and P. micantana (Kennel). Liu (2002) recorded P. plumbeolana (Bremer), but it subsequently was transferred to Clepsis. During field work in South China we discovered an undescribed species in this genus. The purpose of this paper is describe the new species and provide a comparison between it and its closest relative, P. lecheana. A key and the distribution map of Ptycholoma from China are provided.